INSAN TURMISINDA MÁDENIYATTIŃ ROLI - Abdiev, B.T.; Joldasbayev, O.Y.; Jamalov, N.Y.; Biyimbetov, J.Q. (SCIENCE and SOCIETY, 2022)
The article clarifies the culture of the society, its main dimensions and the concept of culture. The peculiarities of culture, its development in the life of society, the influence of culture on human life, the relationship of traditions with customs and their importance in the spiritual maturity of a person are widely explained. These questions are mostly philosophical, with a level analysis of meaning.